Surgical treatment of spondylodiscitis. An update - Guerado, Enrique (Springer-Verlag, 2012)
CONCEPT: Spondylodiscitis refers to an infection affecting the intervertebral disk, the vertebral body or the posterior arch of the vertebra being aetiologically, pyogenic, granulomatous (tuberculosis, brucellosis, or fungal infection) or parasitic. DIAGNOSIS: Spondylodiscitis diagnosis is based on clinical symptoms, a combination of erythrocyte sedimentation rate with C-reactive protein (CRP) tests and, less useful, leukocytosis. Blood culture is also a very cost-effective method of identifying organisms. Plain radiographs are useful, however changes may take several months to appear. Radionuclide tests are currently less used; nevertheless, fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) shows encouraging results particularly when magnetic resonance images (MRI) are unconvincing in the distinction between degenerative changes and infection. MRI with gadolinium enhancement is the choice for image diagnosis. MANAGEMENT: Medical management is usually the basis for treatment, alone or in combination with surgery. Surgical approach, either by endoscopy or open, is indicated for biopsy when clinical evolution is unsatisfactory and no micro-organism has been isolated, and also whenever a root, spinal cord or dural compression is seen on MRI; spinal instability or severe deformity are also clear indications for surgical treatment. Less invasive surgery either CT-scan guided or, particularly, by endoscopy has good results. However open surgery is still the standard. The anterior approach allows for anterior disc and bone debridement. The posterior approach is indicated when posterior elements are involved or in the presence of an epidural abscess. Although good results have been claimed, the use of instrumentation in the presence of an infected focus is controversial, as the use of cages or BMPs are.